2021
DOI: 10.7150/jca.40500
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD1/PDL1 in gastric cancer at different microsatellite status and its correlation with infiltrating immune cells in the tumor microenvironment

Abstract: Objective: The microsatellite status and tumor immune microenvironment have a remarkable influence on tumor immunotherapy. This study was performed to investigate programmed cell death protein 1/programmed death ligand 1 (PD1/PDL1) expression and their correlations with CD8+ T cell/CD68+ macrophage (CD68+ M) densities in gastric cancer (GC) at different microsatellite statuses. Methods: The expression of MLH1, PMS2, MSH2, and MSH6 was detected via immunohistochemistry (IHC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Enriched tumor-infiltrating immune cells (lymphocyte and tumor-associated macrophages) exist in the EBVaGC microenvironment (9,10). The density of CD68+macrophages was significantly higher in EBVaGC patients compared to Epstein-Barr virus-negative gastric cancer (EBVnGC), which was positively correlated with the expression rate of PD-L1 (11,12). Compared with EBVnGC, the density of PD-L1+ tumor infiltrating immune cells was significantly greater in EBVaGC (10).…”
Section: Discussionmentioning
confidence: 99%
“…Enriched tumor-infiltrating immune cells (lymphocyte and tumor-associated macrophages) exist in the EBVaGC microenvironment (9,10). The density of CD68+macrophages was significantly higher in EBVaGC patients compared to Epstein-Barr virus-negative gastric cancer (EBVnGC), which was positively correlated with the expression rate of PD-L1 (11,12). Compared with EBVnGC, the density of PD-L1+ tumor infiltrating immune cells was significantly greater in EBVaGC (10).…”
Section: Discussionmentioning
confidence: 99%
“…Two phase III clinical trials have reported that there is a positive correlation between higher PD-L1 expression in gastric cancer tissues and better treatment outcomes, but negative PD-L1 expression is a negative predictor of pembrolizumab survival benefit [ 21 , 48 ]. Wang et al also pointed out that gastric cancer patients with PD1/PD-L1 high expression may be potential beneficiaries of PD1/PD-L1 immunotherapy [ 49 ]. The upregulation of TIM-3 expression in gastric cancer is associated with poor prognosis, tumor lymph node metastasis, and advanced clinical staging of gastric cancer patients [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of gastric cancer, there are no obvious symptoms. For advanced gastric cancer, traditional surgical resection and chemoradiotherapy have little effect, and so there is still the need to develop effective treatment drugs [12]. Amygdalin was found to possess huge potentials for the treatment of gastric cancer [13].…”
Section: Discussionmentioning
confidence: 99%